Aspirations of students in the diploma music program / Abidsa Yusop - Yusop, Abidsa (Faculty of Music, 2009)
Students aspirations is a term commonly used in education, yet there is little agreement of what it means and even less understanding about its motivation. It is a purpose of this paper to trace the students' aspirations for their enrolment in the Diploma in Music program at UiTM. Sample for this study were 185 diploma students. Questionnaires were distributed to students which consisted of questions that sought to investigate the reasons why they had chosen to study music at UiTM and their aspirations posterior to the completion of their course at UiTM. Findings indicate that most of the students plan to further their study to improve themselves. Bachelors degrees in Music Education and Music Performance are two most chosen programs for further study. Interestingly, female students choose to further in the Music Education while male students prefer the Music Performance program. Interest in music, wanting to make music as a career, the Bumiputera policy and low fees are some of the main reasons why the students chose to pursue their studies in music at UiTM.